Cost-Effectiveness of the Pharmacist-Managed Warfarin Therapy vs. Standard Care for Patients With Mechanical Mitral Valve Prostheses: An Egyptian Healthcare Perspective - Batran, Radwa Ahmed; Sabri, Nagwa Ali; Ali, Ihab; Fahmy, Sarah Farid (Frontiers in Cardiovascular Medicine, 2022)
Background: Despite warfarin therapy had been used for decades for patients with mechanical mitral valve prostheses (MMVPs), serious and life-threatening complications are still reported worldwide with a significant economic burden. This study aimed at assessing the clinical and the cost-effectiveness of adopting the pharmacist-managed warfarin therapy (PMWT) services for optimizing warfarin treatment in Egypt. Methods: A prospective randomized trial in which 59 patients with MMVPs were randomly assigned to receive the PMWT services or the standard care and followed up for one year. The primary outcome was percentage time in therapeutic range (TTR). For the cost-effectiveness analysis, a Markov cohort process model with nine mutually exclusive health states was developed from a medical provider’s perspective. A lifetime horizon was applied. All costs and outcomes were discounted at 3.5% annually. Results: The study results revealed a significantly higher median TTR in the intervention group compared to the control group; 96.8% (IQR 77.9-100%) versus 73.1% (52.7-95.1%), respectively, P= 0.008. A significant association between standard care and poor anticoagulation control (P= 0.021) was demonstrated by the multivariate regression analysis. For the cost-effectiveness analysis, the total cumulative quality-adjusted life-years and total costs per patient were 21.53 and 10.43; 436.38 USD and 1242.25 USD in the intervention and control groups, respectively with an incremental cost-effectiveness ratio (ICER) of -72.5796 for the intervention group. Conclusion: The PMWT strategy was proved to provide a significantly better anticoagulation control and to be a cost-saving approach in Egyptian patients with MMVPs. Nevertheless, the dominance of this strategy is sustained by maintaining the therapeutic INR control within the recommended range. Our findings will benefit Egyptian policy-makers who may seek novel health strategies for better resource allocation.